Effects of Inter and Intra Row Spacing on Growth and Yield Components of Hot Pepper (Capsicum Annum L.) Var Halaba - Markos, Daniel; Mekonen, Shiferaw (Canadian Journal of Agriculture and Crops, 2017)
A field experiment was carried out during 2014 and 2015 growing seasons at Galato research farm located in Halaba, southern Ethiopia to identify optimum plant density (row x plant spacing) that maximize growth and pod yield components of hot pepper. Four row spacing (40, 50, 60 and 70cm) and four plant spacing (20, 30, 40 and 50 cm) were arranged in 4 x 4 factorial combination in Randomized Complete Block Design (RCBD) with three replications. Results indicated that year x row spacing produced more significant (P<0.05) interaction compared to year x plant spacing, row x plant spacing or year x row x plant spacing. Row x plant spacing of 70 cm x 30 cm (47,619 plants/ha), 60 cm x 30 cm (55,555 plants/ha), 50 cm x 30 cm (66,666 plants/ha), 40 cm x 40 cm (62,500 plants/ha) and 40 cm x 50 cm (50,000 plants/ha) produced statistically similar HI results to that of 50 cm x 20 cm row x plant spacing (100,000 plants/ha). Lowest HI was measured due to 40 cm x 20 cm row x plant spacing (125,000 plants/ha). The maximum of 29.3 qt/ha of dry pod yield of hot pepper was measured due to 60 cm wide rows in 2014 (good year) where as the lowest pod yield of 15.4 qt/ha was obtained due to 40 cm wide rows in 2015 (bad year). Dry biomass yield of hot pepper was significantly higher (P<0.05) due to 50 cm wide rows in 2014 where as the lowest dry biomass yield was recorded due to 70 cm wide rows in 2015. Fruit yield/plant showed positive significant correlation with plant height (r=0.572) and pod numbers (r=0.641). Significant negative association was observed between HI (harvest index) and plant height (r=-0.429), and HI and branch number (r=-0.512). Results indicated that significantly higher (P<0.01) dry pod yield in 2014 was obtained due to 60 cm x 20 cm row x plant spacing (83,333plants/ha). However, 50 cm x 30 cm (66,666plants/ha) spacing produced statistically similar dry pod yield to that of 60 cm x 20 cm row x plant spacing. In 2015, dry pod yield was significantly higher (P<0.01) due to 70 cm x 30 cm row x plant spacing (47,617 plants/ha) compared to other row x plant spacing combinations. 60 cm x 30 cm row x plant spacing produced intermediary results in 2015. Thus, hot pepper requires wider row x plant spacing in drier times and narrower row x plant spacing in rainy times under field conditions of Halaba.